2010
DOI: 10.1136/jnnp.2010.226340.21
|View full text |Cite
|
Sign up to set email alerts
|

PATH53 Magnetic susceptibility of substantia nigra in Parkinson's disease: a 7-T in vivo MRI study

Abstract: At post mortem, the hypopigmented substantia nigra (SN) of Parkinson disease (PD) patients generally shows a decrease in neuromelanin (NM) with an increase in ferritin particularly in dopaminergic neurones. Relaxometry-based MRI methods of assessing iron content in the SN depend on the microscopic distribution of iron. Phase mapping or susceptibility weighted imaging methods are sensitive to the magnetic susceptibility and hence iron content of tissue, but both are affected by the geometrical distortion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Treatment of PD by means of deep brain stimulation depends greatly on correct positioning of the stimulating electrode in the target areas. Cho et al [45] showed that 7 T MRI was superior in delineating these areas compared to 1.5 T and 3.0 T. Bajaj et al [46] showed that 7 T MRI could distinguish subregions of the substantia nigra, and found an increased iron content in a part of this basal ganglion in PD patients compared to healthy volunteers. Recently, Oh et al [47] visualized differences in anatomical patterns of the substantia nigra between healthy controls and PD patients with 7 T MRI, possibly enabling earlier diagnosis of PD.…”
Section: Degenerative Brain Diseasesmentioning
confidence: 99%
“…Treatment of PD by means of deep brain stimulation depends greatly on correct positioning of the stimulating electrode in the target areas. Cho et al [45] showed that 7 T MRI was superior in delineating these areas compared to 1.5 T and 3.0 T. Bajaj et al [46] showed that 7 T MRI could distinguish subregions of the substantia nigra, and found an increased iron content in a part of this basal ganglion in PD patients compared to healthy volunteers. Recently, Oh et al [47] visualized differences in anatomical patterns of the substantia nigra between healthy controls and PD patients with 7 T MRI, possibly enabling earlier diagnosis of PD.…”
Section: Degenerative Brain Diseasesmentioning
confidence: 99%
“…Hence, in PD, iron accumulation may mitigate the T1 signal reduction resulting from neuromelanin loss. A recent high‐resolution iron mapping study using susceptibility mapping at 7T suggested a significant but small increase in iron content in patients with PD with significant interindividual and spatial heterogeneity 31. This may contribute to interindividual variability in T1 contrast and underscores the advantage of the proposed areametric method.…”
Section: Discussionmentioning
confidence: 98%